2012
DOI: 10.4049/jimmunol.1201815
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Regulated Availability of RANKL and CD40 Ligand Reveals Distinct Mechanisms of Fetal and Adult Cross-Talk in the Thymus Medulla

Abstract: T-cell tolerance in the thymus is a key step in shaping the developing T-cell repertoire. Thymic medullary epithelial cells play multiple roles in this process including negative selection of autoreactive thymocytes, influencing thymic dendritic cell positioning, and the generation of FoxP3+ Regulatory T-cells. Previous studies show that mTEC development involves haemopoietic crosstalk, and numerous Tumour Necrosis Factor Receptor Superfamily members have been implicated in this process. While CD40 and RANK re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 53 publications
2
56
0
2
Order By: Relevance
“…Therefore, Wip1 may regulate CD40 expression on mTECs to control mTEC development. A recent study has shown that CD40L/CD40 signaling controlled proliferation, but not the rate of apoptosis, within the mTEC compartment (41). These findings are consistent with our results in that Wip1 deficiency caused decreased proliferation but not apoptosis in mTECs.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, Wip1 may regulate CD40 expression on mTECs to control mTEC development. A recent study has shown that CD40L/CD40 signaling controlled proliferation, but not the rate of apoptosis, within the mTEC compartment (41). These findings are consistent with our results in that Wip1 deficiency caused decreased proliferation but not apoptosis in mTECs.…”
Section: Discussionsupporting
confidence: 93%
“…Pendant longtemps, il était admis que l'expression de la protéine était contrôlée par différents facteurs en fonction du stade pré-ou post-natal du thymus. Ainsi, la cytokine RANKL (receptor activator of nuclear factor kappa-B ligand) secrétée par une petite population de cellules CD4 + CD3 -(liées au développement de structures lymphoïdes secondaires organisées et appelées CD4 + 3 -inducer cells) est capable d'induire l'expression de AIRE dans le thymus foetal [14,15]. Chez l'embryon, une population de progéniteurs cellulaires, les invariant V5 + dendritic epidermal T cell progenitors, qui, avec les cellules CD4 + CD3 -, produisent RANKL, participerait au développement des CETm exprimant AIRE [16].…”
Section: Rôle Des Hormones Sexuelles Dans La Régulation De Aireunclassified
“…Chez l'embryon, une population de progéniteurs cellulaires, les invariant V5 + dendritic epidermal T cell progenitors, qui, avec les cellules CD4 + CD3 -, produisent RANKL, participerait au développement des CETm exprimant AIRE [16]. Dans le thymus post-natal, l'induction de l'expression de AIRE par les CETm serait contrôlée par deux voies de transduction : l'une activée par RANKL et l'autre par la cytokine CD40L (ou CD154), une molécule sécrétée par les lymphocytes T CD4 + [15,[17][18][19] (➜). stimulation [7].…”
Section: Rôle Des Hormones Sexuelles Dans La Régulation De Aireunclassified
“…Presumably this would facilitate more interactions between the proTs and mTECs. This crosstalk provides important stimulatory signals for mTECs, which turn over every 10 to 14 days (47,48), through receptor activator of NF-κB, RANKL, CD80/86, LTβR, and CD40 (26,(49)(50)(51)(52). The difference in effects on short-term and long-term thymopoiesis and TEC recovery seen between differing input populations of proTs would suggest that using a combination of DN2 and DN3 proTs may be an optimum approach.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, TECs also depend on interactions with developing T cells in order to develop, proliferate, and persist (15,(24)(25)(26). Conditioning eliminates developing thymocytes, and, in order to generate new T cells, there is a reliance on HSC-derived progenitors to home to and differentiate to T cell progenitors (proTs) within the thymus.…”
Section: Introductionmentioning
confidence: 99%